ADP-Ribosylation Factor Family of Small GTP-Binding Proteins: Their Membrane Recruitment, Activation, Crosstalk and Functions - Li, Tiantian; Guo, Yusong (Frontiers in Cell and Developmental Biology, 2022)
Members of the ADP-ribosylation factor (ARF) family of guanine-nucleotide binding proteins play critical roles in various cellular processes, especially in regulating the secretory and endocytic pathways. The fidelity of intracellular vesicular trafficking depends on proper activations and precise subcellular distributions of ARF family proteins regulated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). Recently, structural, functional, and mechanistic studies have provide novel insights into how Arf proteins perform their cellular functions. Here we review recent progresses in understanding the membrane recruitments, activation, crosstalk, and functions of ARF family proteins.